Patients Admitted to Tertiary Health Care Center: Cancer Screening Program Awareness Study - Gamze Gokoz Dogu; Aysegul Atceken; Gizem Cetinkaya; Merve Oner; Nazire Nagihan Yagın; Ahmet Ergin (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2017)
Background: Screening programs for detecting cancer early are critically important for a better prognosis and a long acting survival. In our country, second most common cause of death is cancers with the rate of 21.1 %. The aim of this study was to investigate cancer screening and awareness in healthy individuals in our region.  Study Design: The survey was conducted on 400 randomly selected patients who were admitted to Pamukkale University hospital with the method of face to face interview in May 2016 Statistical evaluation was performed using SPSS v22.  Results: Of the 400 participants, 192 (45%) were male, and 208 (52%) were female. We found out that stated that they had heard the cancer screening programs 65% and KETEM- Cancer Early Diagnosis and Training Centers name units in Turkey = Kanser Erken Tanı, Tarama ve Eğitim Merkezi - (18,5%).   Only 31.7% of the participants knew the the cancer screening and the proportion who answered correctly was higher among less than 30 years old (p=0.007) Early diagnosis and treatment of cancer is most of the time lifesaving. In our study we saw that most of the people had less and missing knowledge about cancer early diagnosis. People who had a history of cancer in their family had much more knowledge about cancer screening tests. Of the 81.5% participants had not heard about KETEM, and 35% had not heard about the cancer screening programs. Conclusion: Awareness studies for relatives of patients with cancer should be conducted. Due to low rates of correct answers were given to the questions of methods for screening methods, our people should be informed about cancer screening.